Molecular characterization of the Escherichia coli enterobactin cistron entF and coupled expression of entF and the fes gene. - Pettis, G S (1987)
The Escherichia coli entF gene, which encodes the serine-activating enzyme involved in enterobactin synthesis, has been localized to a 4.7-kilobase-pair DNA fragment inserted in the vector pBR328. This recombinant molecule, pITS32, restored the ability of an entF mutant to grow on low-iron medium and to produce enterobactin. Examination of its translation products by minicell and electrophoretic analyses revealed a protein of approximately 160,000 daltons, which we identified as the EntF protein. A small DNA segment from pITS32 containing the translational start site for entF allowed the low constitutive expression of beta-galactosidase when cloned (pITS301) upstream of the lacZ structural gene in the vector pMC1403. In contrast, a clone (pITS312) containing the identical entF-lacZ fusion and a larger region upstream of entF including the entire fes gene and extending into the fepA gene (whose transcription is in the opposite direction relative to entF) expressed beta-galactosidase in high yet inducible amounts in response to fluctuations in the metabolic iron concentration. Transposon insertion mutations in the fes gene but not an insertion near the 5' region of fepA in pITS312 reduced this high inducible expression to the low constitutive level seen for pITS301. These observations are most readily explained by the presence of a regulatory region located upstream of fes which mediates the iron-regulated expression of a transcript that includes the fes and entF genes.